2000
DOI: 10.1038/sj.onc.1203733
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-histochemical detection of human telomerase reverse transcriptase in human liver tissues

Abstract: Although telomerase activity in hepatocellular carcinoma (HCC) increases in accordance with degree of histological undi erentiation, it is unknown whether the level of telomerase activity in HCC re¯ects of the degree of activity in individual cells or the frequency of telomerasepositive HCC cells. Non-cancerous liver tissues exhibit low but signi®cant levels of telomerase activity, but the nature of telomerase-positive cells in these tissues is unclear. In this study, we performed immunohistochemical staining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 31 publications
5
27
0
Order By: Relevance
“…Reactivation of telomerase activity is a characteristic molecular mechanism in hepatocarcinogenesis and it has been shown that hTERT is overexpressed in f80% to 100% of human HCCs (16)(17)(18). We and others recently showed that the hTERT-promoter can be used to generate tumor-specific replicating vectors for safe and effective virotherapy of telomerase-positive cancers (19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…Reactivation of telomerase activity is a characteristic molecular mechanism in hepatocarcinogenesis and it has been shown that hTERT is overexpressed in f80% to 100% of human HCCs (16)(17)(18). We and others recently showed that the hTERT-promoter can be used to generate tumor-specific replicating vectors for safe and effective virotherapy of telomerase-positive cancers (19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…28 The recent development of antibodies directed against hTERT, applicable to formalin-fixed, paraffin-embedded sections is very promising in identifying precisely which cells within a given tumor express hTERT. 29,30 Telomeric repeat lengths (TRF lengths) were measured in 2 different samples of all 37 STSs and an attempt was made to correlate TRF lengths with TA, hTERT mRNA expression, tumor histology, grade and proliferative activity. In every case, tumor TRF lengths were compared to normal striated muscle TRFs from 10 tumor-free patients, of which the mean size was 12 kbp.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that hTERT interactions with telomeres may influence the association between telomeres and nuclear matrix. Recently, we and others have shown that hTERT is present throughout the nucleus but in certain instances hTERT is concentrated in the nucleolar organizing region (Tahara et al, 1999;Vaziri et al, 1999;Kawakaim et al, 2000;Wood et al, 2001;Etheridge et al, 2002). More directly, telomeres have been shown cytologically as well as biochemically to be tethered to the nuclear matrix (Smith and de Lange, 1997;Pandita, 2002).…”
Section: Htert Expression Influences Telomere-nuclear Matrix Associationmentioning
confidence: 99%